(untitled) (Dimensión Empresarial, 2017)
Review and comments of the book The Creation of a Learning Society of the Nobel Prize Joseph Stiglitz. Resumen Revisión y comentarios del libro La Creación de una Sociedad del Aprendizaje del premio Nóbel Joseph Stiglitz. Resumo Revisão e comentários do livro A Criação de uma Sociedade de Aprendizagem do Prêmio Nobel Joseph Stiglitz.